Nanomaterials - Ghatak, Kamakhya Prasad (De Gruyter, 2020)
This monograph investigates the entropy in heavily doped (HD) quantized structures by analyzing under the influence of magnetic quantization, crossed electric and quantizing fields the range from HD quantum confined nonlinear optical materials to HgTe/CdTe HD superlattices with graded interfaces. Finally the authors address various challenges in today's research of optoelectronic materials and give an outlook to future studies